Pharmacy education in Nigeria: The journey so far - Joshua Ikoni Ogaji; Candidus Ejembi Ojabo (Archives of Global Professionals, 2014)
The last four decades have witnessed developmental changes in pharmacy education in Nigeria. The paradigm change in the role of the pharmacist from a product-oriented to patient-oriented focus requires that the overall education of pharmacists be reorganized to meet the increasing changing roles. Curricular of schools of pharmacy in Nigeria are continually reviewed with the aim of attaining the dynamic competency required to reflect the paradigm shift in service focus and the development of the necessary clinical skills that will enable pharmacists to identify and meet the increasingly complex medication needs of patients. This review focuses on the historical development of pharmacy education from one school of pharmacy in the 1920s to about twenty schools 40 years later. The study looked at the continuous efforts made to produce the pharmacist with the requisite competency for the ever-changing roles in meeting the dynamic and varied needs of patients.